2017
DOI: 10.1172/jci90921
|View full text |Cite
|
Sign up to set email alerts
|

Lysine methyltransferase SMYD2 promotes cyst growth in autosomal dominant polycystic kidney disease

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is driven by mutations in PKD1 and PKD2 genes. Recent work suggests that epigenetic modulation of gene expression and protein function may play a role in ADPKD pathogenesis. In this study, we identified SMYD2, a SET and MYND domain protein with lysine methyltransferase activity, as a regulator of renal cyst growth. SMYD2 was upregulated in renal epithelial cells and tissues from Pkd1-knockout mice as well as in ADPKD patients. SMYD2 deficiency delayed renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
119
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(128 citation statements)
references
References 55 publications
(71 reference statements)
6
119
0
Order By: Relevance
“…In this regard, the expression of the histone methyltransferase, EZH2, is increased in UUO and in CKD patients and its pharmacological inhibition reduced preclinical fibrosis (Zhou et al, 2016). Similar results were found for the histone methyltransferase, SMYD2 in clinical and preclinical PKD (Li et al, 2017). In AKI induced by IRI or endotoxin, increased histone methylation has been linked to the increased expression of proinflammatory and pro-fibrotic genes (Naito et al, 2008;Zager and Johnson, 2009).…”
Section: Epigenetic Modifications In Renal Injurysupporting
confidence: 59%
“…In this regard, the expression of the histone methyltransferase, EZH2, is increased in UUO and in CKD patients and its pharmacological inhibition reduced preclinical fibrosis (Zhou et al, 2016). Similar results were found for the histone methyltransferase, SMYD2 in clinical and preclinical PKD (Li et al, 2017). In AKI induced by IRI or endotoxin, increased histone methylation has been linked to the increased expression of proinflammatory and pro-fibrotic genes (Naito et al, 2008;Zager and Johnson, 2009).…”
Section: Epigenetic Modifications In Renal Injurysupporting
confidence: 59%
“…Our previous ChIP-seq data indicated that PTPN13 was regulated by SMYD2 via the methylation of histones 29 , which regulates a variety of cellular processes and oncogenic transformation by removing phosphate groups from phosphorylated tyrosine residues on a number of proteins, including ERK and STAT 30 , 31 . SMYD2 is able to downregulate the expression of PTPN13 in TNBC cells (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…responsible for protein-protein interactions with a prolinerich motif (PXLXP) (Arsenault et al 2016;Calpena et al 2015;Mazur et al 2016;Spellmon et al 2015). In mammals, there are five members of the SMYD family, SMYD1-5, with distinct biological functions (Al-Shar'i and Alnabulsi 2016; Bagislar et al 2016;Giakountis et al 2017;Li et al 2017;Spellmon et al 2015). SMYD1 is involved in cardiac development and in skeletal muscle growth and regeneration, by interacting with muscle-specific transcription factor skNAC or methylating histone H3K4 (Du et al 2014;Rasmussen et al 2015).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The lysine methyltransferase SMYD contains a conserved SET domain (Drosophila proteins Suppressor of variegation, Enhancer of Zeste, Trithorax) responsible for catalyzing lysine methylation (Herz et al 2013;Qian and Zhou 2006). This SET domain is interrupted by a MYND domain (Myeloid, Nervy and DEAF-1) (Al-Shar'i and Alnabulsi 2016; Calpena et al 2015;Li et al 2017) which is mainly Edited by Jiamei Li.…”
Section: Introductionmentioning
confidence: 99%